2010
DOI: 10.1159/000314876
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Diabetic Retinopathy in Egypt: A Hospital-Based Study

Abstract: Purpose: To determine the prevalence and determinants of diabetic retinopathy (DR) in patients ≧18 years at the Cairo University and Sixth of October University hospitals. Patients and Methods: This is a cross-sectional survey among known diabetic patients attending diabetic clinics. Patients were randomly selected to complete an interviewer-administered questionnaire and a medical assessment. All patients had a dilated fundus examination for evidence of DR using slit-lamp biomicroscopy. Results: A sample of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 55 publications
7
41
5
Order By: Relevance
“…Among younger-onset patients with diabetes in the Wisconsin Epidemiologic Study of DR, the prevalence of any retinopathy was 8% at 3 years, 25% at 5 years, 60% at 10 years and 80% at 15 years respectively. [1] Our findings are consistent with Macky et al .,[18] reported that the prevalence of DR was statistically significantly higher with longer diabetes disease duration ( P < 0.001). Hohenstein et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among younger-onset patients with diabetes in the Wisconsin Epidemiologic Study of DR, the prevalence of any retinopathy was 8% at 3 years, 25% at 5 years, 60% at 10 years and 80% at 15 years respectively. [1] Our findings are consistent with Macky et al .,[18] reported that the prevalence of DR was statistically significantly higher with longer diabetes disease duration ( P < 0.001). Hohenstein et al .…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, female preponderance was evident which is consistent with Macky et al . ;[18] who found that the prevalence of DR was statistically significantly higher in females (22 vs. 17%, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herman et al3 found that diabetic retinopathy accounted for about 42% of diabetic patients in Egypt; however, the study done by Macky et al4 found the incidence to be 20.5%. This improvement could be attributed to early detection of diabetic patients, with better medical care 3,4.…”
Section: Introductionmentioning
confidence: 96%
“…This improvement could be attributed to early detection of diabetic patients, with better medical care 3,4. The duration of diabetes remains the most significant predictor of visual impairment among people with type II diabetes.…”
Section: Introductionmentioning
confidence: 99%